Emulation of gas-liquid flow in packed beds for offshore floating applications using a swell simulation hexapod - Assima, Gnouyaro P.; Motamed-Dashliborun, Amir; Larachi, Faïçal (AIChE journal, 2015)
A laboratory‐scale packed column was positioned on a six degree of freedom swell simulation hexapod to emulate the hydrodynamics of packed bed scrubbers/reactors onboard offshore floating systems. The bed was instrumented with wire mesh capacitance sensors to measure liquid saturation and velocity fields, flow regime transition, liquid maldistribution, and tracer radial and axial dispersion patterns while robot was subject to sinusoidal translation (sway, heave) and rotation (roll, roll + pitch, yaw) motions at different frequencies. Three metrics were defined to analyze the deviations induced by the various column motions, namely, coefficient of variation and degree of uniformity for liquid saturation fluctuating fields, and effective Péclet number. Nontilting oscillations led to frequency‐independent maldistribution while tilting motions induced swirl/zigzag secondary circulation and prompted nonuniform maldistribution oscillations that deteriorated with decreasing frequencies. Regardless of excited degree of freedom, a qualitative loss of plug‐flow character was observed compared with static vertical beds which worsened as frequencies decreased. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2354–2367, 2015